Faktor-faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi: kemuktakhiran Teknologi, Kemampuan Teknik Personal Sistem Informasi, Program Pelatihan Pengguna dan Dukungan Manajemen Puncak - Bunga Aprilia Salsabilla Anwar; Cris Kuntadi; Rachmat Pramukty (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that affect the Performance of Accounting Information Systems, namely the latest technology, Information Systems Personal Engineering Capabilities, User Training Programs and Top Management Support, a financial management literature study. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) cutting-edge technology affects the performance of accounting information systems; 2) Technical Ability of Personal Information Systems affects the Performance of Accounting Information Systems; 3) User Training Programs affect the Performance of Accounting Information Systems; 4) Top Management Support affects the Performance of Accounting Information Systems.